Delivering perinatal depression care in a rural obstetric setting: a mixed methods study of feasibility, acceptability and effectiveness. (2nd October 2018) - Bhat, Amritha; Reed, Susan; Mao, Johnny; Vredevoogd, Mindy; Russo, Joan; Unger, Jennifer; Rowles, Roger; Unützer, Jürgen
Abstract: Objectives: Universal screening for depression during pregnancy and postpartum is recommended, yet mental health treatment and follow-up rates among screen-positive women in rural settings are low. We studied the feasibility, acceptability and effectiveness of perinatal depression treatment integrated into a rural obstetric setting. Methods: We conducted an open treatment study of a screening and intervention program modified from the Depression Attention for Women Now (DAWN) Collaborative Care model in a rural obstetric clinic. Depression screen-positive pregnant and postpartum women received problem-solving therapy (PST) with or without antidepressants. A care manager coordinated communication between patient, obstetrician and psychiatric consultant. We measured change in the Patient Health Questionnaire 9 (PHQ-9) score. We used surveys and focus groups to measure patient and provider satisfaction and analyzed focus groups using qualitative analysis. Results: The intervention was well accepted by providers and patients, based on survey and focus group data. Feasibility was also evidenced by recruitment (87.1%) and retention (92.6%) rates and depression outcomes (64% with >50% improvement in PHQ 9) which were comparable to clinical trials in similar urban populations. Conclusions for practice: DAWN Collaborative Care modified for treatment of perinatal depression in a rural obstetric setting is feasible and acceptable. Behavioral health services integrated into rural obstetric settings could improve care for perinatal depression.